2019
DOI: 10.1177/1074248419876632
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Undercarboxylated Osteocalcin Upregulation in Microvascular Insufficiency in a Rat Model of Diabetic Cardiomyopathy

Abstract: Background: Diabetic cardiomyopathy (DCM) is accompanied by microvascular complications that lead to myocardial dysfunction and heart failure. Most conventional therapies cannot ameliorate the microvascular insufficiency in DCM. In this study, we tested the hypothesis that undercarboxylated osteocalcin (ucOC) may be a new adjuvant therapy against the progression of DCM and its underlying microvascular pathology. Materials and Methods: Diabetes was induced in Wistar rats with a high-fat diet combined with strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…These findings strengthen our above-mentioned results, suggesting that serum levels of ucOC could be a potential biomarker to estimate cardiovascular and T2D risk in MetS patients. In addition, based on the aforementioned evidences, in the future, ucOC might become a therapeutic target to prevent cardiovascular events as reported by recent studies conducted in animal models 52,53 .…”
Section: Discussionmentioning
confidence: 94%
“…These findings strengthen our above-mentioned results, suggesting that serum levels of ucOC could be a potential biomarker to estimate cardiovascular and T2D risk in MetS patients. In addition, based on the aforementioned evidences, in the future, ucOC might become a therapeutic target to prevent cardiovascular events as reported by recent studies conducted in animal models 52,53 .…”
Section: Discussionmentioning
confidence: 94%
“…Some studies showed ucOC was a main bioactivity form of OC, contributing to the regulation in glucose homeostasis and energy metabolism [ 99 , 100 ]. Another study showed ucOC improved microvascular insufficiency and myocardial dysfunction in a rat diabetic cardiomyopathy model [ 101 ]. However, the following studies have challenged these findings by showing no endocrine abnormalities in OC-deficient mice [ 102 , 103 ].…”
Section: Main Textmentioning
confidence: 99%
“…Unlike ucOC metabolic functions, OC mechanistic insights in cardiovascular health are fewer and equivocal. Several animal studies have suggested that ucOC may protect vasculature under T2D conditions ( Figure 1 ) [ 14 , 57 , 58 ]. For instance, ucOC administration improved diastolic blood pressure, endothelium-dependent relaxation, and aortic atherosclerotic plaque formation in high-fat diet (HFD)-fed apolipoprotein E (ApoE) −/− mice [ 14 ].…”
Section: Chronic Inflammation During the Development Of Type 2 Diabetmentioning
confidence: 99%
“…For instance, ucOC administration improved diastolic blood pressure, endothelium-dependent relaxation, and aortic atherosclerotic plaque formation in high-fat diet (HFD)-fed apolipoprotein E (ApoE) −/− mice [ 14 ]. In diabetic rats, the enhancement of circulatory ucOC, either by ucOC or warfarin administration, improved arterial stiffness, vascularization, capillary density, and neovascularization and decreased myocardial fibrosis [ 57 , 58 ]. However, whether these improvements are from ucOC acting directly on vascular cells or are as a consequence of improved metabolic outcomes remains unknown.…”
Section: Chronic Inflammation During the Development Of Type 2 Diabetmentioning
confidence: 99%